Croquis de correctionnelle - Goldstein, Estelle; Soudan, Eugène; Paulus, Jean-Pierre (Bruxelles : Wellens-Pay, 1948)
Bibliotheek Camille Huysmans
Dedicator: Goldstein, Estelle, dedicatee: Huysmans, Camille
Frans
Monografie